Evaluation of the Effects of Age, Sex, and Dexpanthenol-Containing Skin Care on the Facial and Body Skin Microbiome - Zainab Qaizar; Raffaella de Salvo; Gregor Bieri; Katrin Unbereit; Shannon Montgomery; Erwan Peltier (Cosmetics)
Given the pivotal role played by the microbiome in skin health, it is important to understand how its composition varies with age, sex, and body site and regular use of topical products. Four studies were carried out to determine the effects of long-term (4-week) use of different dexpanthenol-containing topical products on the skin microbiome of a varied population with cosmetically dry skin. The skin microbiome composition was assessed before and after product usage. No significant changes in microbiome richness or diversity were found for the individual test products; however, a meta-analysis of the combined dataset did show changes in microbiome composition as a function of the subject’s sex, age, and body site. The work presented here demonstrates how the use of carefully formulated topical products on skin, when used in a way that is representative of real-life usage conditions, can respect the microbial diversity present on skin across a widely varied study population.